2017
DOI: 10.1177/0008417417711459
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between adolescent body mass index, physical activity, and sensory-processing patterns

Abstract: Occupational therapists should consider an adolescent's sensory preferences when recommending PA interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…One article refers to obsessive-compulsive disorder (Rieke & Anderson, 2009). Only one article refers to a skin problem (Engel-Yeger et al, 2011) and another article refers to body mass index (Delahunt & Mische Lawson, 2017). One article refers to youth at high clinical risk for psychosis compared to youth at low risk for psychosis and the general population (Parham et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…One article refers to obsessive-compulsive disorder (Rieke & Anderson, 2009). Only one article refers to a skin problem (Engel-Yeger et al, 2011) and another article refers to body mass index (Delahunt & Mische Lawson, 2017). One article refers to youth at high clinical risk for psychosis compared to youth at low risk for psychosis and the general population (Parham et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Un artículo se refiere a trastorno obsesivo compulsivo (Rieke & Anderson, 2009). Un artículo se refiere a un problema de la piel (Engel-Yeger et al, 2011), otro artículo se refiere a índice de masa corporal (Delahunt & Mische Lawson, 2017). Un artículo se refiere a jóvenes de alto riesgo clínico para la psicosis comparado con jóvenes de bajo riesgo para la psicosis y población general (Parham et al, 2019).…”
Section: Utilización Del Perfil Sensorial Adolescentes/adultos (Brown...unclassified
“…The sensory properties of food (taste, smell, texture, color, and appearance) affect our choices, as well as how much we eat [ 15 ]. Studies of children with an altered sensory profile in other populations, such as children with autistic spectrum disorder, have shown that they may exhibit selective, avoidant, or preferential behavior toward certain foods based on their sensory characteristics or specific brands, and may develop problems such as weight loss, adding to the frustration of their parents and family [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%